Review of research on Bond–Slip of reinforced concrete structures. (3rd July 2023) - Zheng, Yuanxun; Fan, Congcong; Ma, Junjie; Wang, Shaoqiang
Highlights: 184 papers are reviewed on the bond-slip properties of reinforced concrete. The bond-slip mechanics model for concrete and reinforcement under corrosive, temperature, load and stress environments is outlined. The principles and applications of stick–slip detection techniques for reinforced concrete structures are reviewed. Research progress of bond-slip mechanical constitutive relationships and numerical simulations of reinforced concrete structures are discussed. Research prospects for the performance and damage detection of reinforced concrete bonded slip structures are prospected. Abstract: Based on a review of existing literature, this paper summarizes the research progress pertaining to the bond–slip in reinforced concrete (RC) structures. Specifically, considering the characteristics of bond–slip failures, constitutive relations, and experimental methods, the influences of reinforcement properties, concrete properties, stresses, loading modes, and temperature conditions on the bond–slip behaviors of RC structural members are summarized herein. Further, the main problems and future development trends of research on the bond–slip in RC structures are discussed. According to the bond–slip failure characteristics of RC structures, application scenarios of technologies for monitoring slip damage are determined, and the future research directions are also analyzed. Finally, theoretical analysis models and finite-element numerical analysis methods for RC structures are discussed; the advantages and disadvantages of each method are compared and analyzed as well. Considering the existing findings, research on the bond–slip failures of RC suffers from the following limitations: relatively few studies consider the coupling of stick–slip factors, previously proposed constitutive relationships are not widely applicable, and studies based on theoretical analyses are not comprehensive. Accordingly, this paper summarizes the test methods and research results of domestic and foreign research pertaining to the bonding performance of RC members; moreover, the limitations of existing research are also analyzed to provide a reference for further improvements in the basic theoretical system of RC.